Arctic sea ice radar freeboard from ERS-2, Envisat and CryoSat-2 - Bocquet, Marion; Fleury, Sara (Zenodo, 2023)
This dataset presents a radar freeboard time series from 1995 to 2021 for Arctic sea ice. Envisat and ERS-2 radar freeboards have been estimated using CryoSat-2 as a reference, they are "SAR-like" estimationsas they have been calibrated on CS-2 SAR TFMRA50 radar freeboard.